An investigation of antigenic drift of neuraminidases of influenza A (H1N1) viruses. - Luther, P. (Cambridge University Press, 1984)
A newly developed lectin neuraminidase test (LNT) and a panel of mouse monoclonal and post-infection ferret antibodies have been used to analyse antigenic drift in N1 neuraminidases of influenza A viruses isolated between 1933 and 1957 and also between 1977 and 1980. Significant antigenic differences were detected among the 'early' (1933-57) viruses since the NA of viruses isolated one year apart could be distinguished serologically. The NA of the 're-emerged' virus A/USSR/92/77 (H1N1) was antigenically related but not identical to influenza A viruses isolated in 1949 (A/Paris/49 (H1N1), A/Geneva/49 (H1N1) which thus predates the previously observed antigenic similarity of A/USSR/77 with A/FW/50 (H1N1) virus.